Sexual transmission of American Trypanosomes from males and females to naive mates - Almeida, Adriana B. (2019)
American trypanosomiasis is transmitted to humans by triatomine bugs through the ingestion of contaminated food, by blood transfusions or accidently in hospitals and research laboratories. In addition, the Trypanosoma cruzi infection is transmitted congenitally from a chagasic mother to her offspring, but the male partner's contribution to in utero contamination is unknown. The findings of nests and clumps of amastigotes and of trypomastigotes in the theca cells of the ovary, in the goniablasts and in the lumen of seminiferous tubules suggest that T. cruzi infections are sexually transmitted. The research protocol herein presents the results of a family study population showing parasite nuclear DNA in the diploid blood mononuclear cells and in the haploid gametes of human subjects. Thus, three independent biological samples collected one year apart confirmed that T. cruzi infections were sexually transmitted to progeny. Interestingly, the specific T. cruzi antibody was absent in the majority of family progeny that bore immune tolerance to the parasite antigen. Immune tolerance was demonstrated in chicken refractory to T. cruzi after the first week of embryonic growth, and chicks hatched from the flagellate-inoculated eggs were unable to produce the specific antibody. Moreover, the instillation of the human semen ejaculates intraperitoneally or into the vagina of naive mice yielded T. cruzi amastigotes in the epididymis, seminiferous tubule, vas deferens and uterine tube with an absence of inflammatory reactions in the immune privileged organs of reproduction. The breeding of T. cruzi-infected male and female mice with naive mates resulted in acquisition of the infections, which were later transmitted to the progeny. Therefore, a robust education, information and communication program that involves the population and social organizations is deemed necessary to prevent Chagas disease.